Gharar, Fraud and Dispute in Islamic Business Transaction an Islamic Law Perspectives - Ahmad Farikhin; Heni Mulyasari (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2022)
Islam adheres to the principle of justice in carrying out muamalah activities, especially in the economic field. Fairness is the main principle and foundation of business relationships between sellers and buyers. Fair means that business activities must be fair and mutually beneficial and do not cause harm to one party, so that the injured party feels aggrieved by the other party. One practice that may harm one party in a business is the practice of gharar. Gharar is an attempt to gain profit illegally way according to Islamic law because it causes the transfer of rights in a false way which has been strictly forbidden by Allah Subhanawu wa Ta'ala. Although Muslim scholars and scholars differ in expressing the definition of gharar, it explicitly has a mutual meaning. In Islamic legal texts fraud (tadlis or khilaba), lesion or misrepresentation (ghabn), gross misrepresentation (ghabn fahish), deception (shushsh), imbalance (gharar), and trickery (taghrir) are used interchangeably as to mean fraud. Such practices can lead to disputes. This research uses a descriptive qualitative method by studying the literature, both classical, contemporary, and scientific journals. The results of the study found that gharar was forbidden because of the presumption between the two transacting parties. Disputes are a danger that will lead to bloodshed between Adam's children and grandchildren. The danger must be removed (al-dhararuu yuzalu). Thus the unavoidable minor gharar caused by unavoidable gharar is unavoidable and unavoidable transactions that have been agreed upon between the seller and the buyer. Keywords: Dispute, Fraud, Gharar, Islamic Business, Customer Satisfaction